Relationship of Social Media to Beauty Insecurity in Generation Z Women - Rosmiati Rosmiati; Dedi Supriadi; Risma Rizatul Jannah (Asy-Syifa : Journal of Science and Technology Nursing, 2023)
Purpose: this study was to determine the relationship of social media to beauty insecurity in generation z women. Methods : The method is quantitative, with a cross-sectional approach, data collection using a questionnaire distributed through Google form. Participants in this study amounted to 50 respondents. This research was conducted in March 2022. Results: the results of the study, out of 50 respondents who do not actively use social media, only 3 people (6%) had a positive impact. While active users of social media are 47 people (94%) with 16 people (32%) getting a positive impact from beauty insecurity and 31 people (62%) getting a negative impact from beauty insecurity. The most widely used social media is WhatsApp as many as 50 people (100%) while the least used is Facebook as many as 26 people (52%). It can be seen that the majority of women from generation z are active users of social media as many as 47 people (94%). Of the 50 respondents with the highest score, 38 (76%) felt the negative impact of beauty insecurity and the results of the Chi-Square statistical test obtained -value (0.003) < value (0.05). Conclusion: The conclusion of this study is that the highest frequency of the negative impact of beauty insecurity is 38 respondents with 76%. The social media with the highest frequency is WhatsApp with 100%. Thus, there is a significant relationship between social media and beauty insecurity in generation z women by obtaining a value (0.003).